Pengelolaan Pembelajaran Holistik pada Pelajaran Pendidikan Agama Islam di Kelas VII SMP Darul Hikam Bandung - Aji Nuryana; Aep Saepudin; Khambali (Bandung Conference Series: Islamic Education, 2022)
Abstract. Education occupies a crucial role in Islam. One of the virtues of Islam for mankind is its comprehensive and consistent method of mental education, giving birth to a rabbinic generation, fostering people and culture and enforcing principles and honors. Holistic Learning is one alternative that helps institutions to produce graduates who are complete both in terms of cognitive, affective and psychomotor. One of the schools that has a holistic curriculum design is SMP Darul Hikam Bandung. The purpose of this research is to find out how to manage holistic learning especially for Islamic Religious Education lessons starting from planning, implementation and assessment. Obtained from this study, the management of holistic learning at SMP Darul Hikam Bandung is in accordance with the principles of holistic learning by modifying the official curriculum and the typical school curriculum to form TCB (Taqwa Character Building)-based moral education and habituation of daily worship so as to shape the student's personality. intelligent and religious. Abstrak. Pendidikan menempati hal yang krusial di dalam agama islam. Salah satu keutamaan islam bagi umat manusia adalah metodenya yang paripurna dan konsisten dalam mendidik mental, melahirkan generasi rabbani, membina umat dan budaya serta memberlakukan prinsip-prinsip dan kemuliaan. Pembelajaran Holistik adalah salah satu alternatif yang membantu lembaga dalam mencetak lulusan yang paripurna baik dari segi kognitif, afektif dan psikomotorik. Salah satu sekolah yang memiliki desain kurikulum holistik adalah SMP Darul Hikam Bandung. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana pengelolaan pembelajaran holistik terkhusus untuk pelajaran Pendidikan Agama Islam dimulai dari perencanaan, pelaksanaan dan penilaian. Hasil yang diperoleh dari penelitian ini bahwasannya pengelolaan pembelajaran holistik di SMP Darul Hikam Bandung sesuai dengan prinsip-prinsip pembelajaran holistik dengan memodifikasi kurikulum dinas dan kurikulum khas sekolah sehingga terbentuk pendidikan akhlak berbasis TCB(Taqwa Character Building) dan pembiasaan ibadah harian sehingga membentuk kepribadian siswa yang pintar dan religius.